Vitamin and mineral supply in children: a pediatrician's view - L.S. Starostina (LCC «Medicine-Inform», 2020)
L.S. Starostina I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation The important role of vitamins for bodily functions was described for the first time by Russian pediatrician N.I. Lunin as early as in 1880. Since then, doctors, biologists, researchers, and other experts have focused on the effects of vitamins on human body and their role in various processes. In 2017, the Union of Pediatricians of Russia has developed "National program of the optimization of vitamin and mineral supply of Russian children" based on the monitoring of child nutrition. Treatment of multivitamin deficiency involves additional intake of missing substances as well as the improvement of their absorption and their synthesis in human body. The vast majority of vitamin and mineral supplements contain daily-recommended amounts of essential vitamins and microelements. However, not all substances are completely absorbed since patients with multivitamin deficiency often have gut microbiome abnormalities resulting in poor availability of s upplemented vitamins and minerals. This paper discusses the rationale of additional vitamins, their role in bodily functions, and signs of vitamin deficiency. Keywords: children, prevention, vitamins, microelements, macroelements, micronutrients, harmonious development, immunity, microbiota, Bifidobacterium. For citation: Starostina L.S. Vitamin and mineral supply in children: a pediatrician's view. Russian Journal of Woman and Child Health. 2020;3(4):319-324. DOI: 10.32364/2618-8430-2020-3-4-319-325.